The pH sensitivity of Aqp0 channels in tetraploid and diploid teleosts. Issue 5 (9th February 2015) - Chauvigné, Francois; Zapater, Cinta; Stavang, Jon Anders; Taranger, Geir Lasse; Cerdà, Joan; Finn, Roderick Nigel
ABSTRACT: Water homeostasis and the structural integrity of the vertebrate lens is partially mediated by AQP0 channels. Emerging evidence indicates that external pH may be involved in channel gating. Here we show that a tetraploid teleost, the Atlantic salmon, retains 4 aqp0 genes ( aqp0a1, ‐0a2, ‐0b1, and ‐0b2 ), which are highly, but not exclusively, expressed in the lens. Functional characterization reveals that, although each paralog permeates water efficiently, the permeability is respectively shifted to the neutral, alkaline, or acidic pH in Aqp0a1, ‐0a2, and ‐0b1, whereas that of Aqp0b2 is not regulated by external pH. Mutagenesis studies demonstrate that Ser 38, His 39, and His 40 residues in the extracellular transmembrane domain of α‐helix 2 facing the water pore are critical for the pH modulation of water transport. To validate these findings, we show that both zebrafish Aqp0a and ‐0b are functional water channels with respective pH sensitivities toward alkaline or acid pH ranges and that an N‐terminal allelic variant (Ser 19 ) of Aqp0b exists that abolishes water transport in Xenopus laevis oocytes. The data suggest that the alkaline pH sensitivity is a conserved trait in teleost Aqp0 a‐type channels, whereas mammalian AQP0 and some teleost Aqp0 b‐type channels display an acidic pH permeation preference.—Chauvigné, F., Zapater, C., Stavang, J. A., Taranger, G. L., Cerdà, J., Finn, R. N. The pH sensitivity of Aqp0 channels in tetraploid and diploid teleosts. FASEB J. 29, 2172‐2184 (2015). www.fasebj.org